Characteristics of Escherichia Coli К Lipopolysacharide - Varbanets, L.D.; Brovarskaya, О.S.; Garkava, К.G.; Tymoshenko, U.V.; Варбанець, Л.Д.; Броварська, О.С.; Гаркава, К.Г.; Тимошенко, У.В. (PH "Akademperiodyka" of the NAS of Ukraine, 2024)
Previously, the authors isolated from the intestine of the chestnut moth caterpillars two cultures of bacteria – Pseudomonas putida and Escherichia coli. Since in interactions with plants or other living beings, lipopolysaccharides are involved, earlier we have characterized the lipopolysaccharide of one of the strains – Pseudomonas putida. The aim of this study was to characterize the lipopolysaccharide of a new strain of Escherichia coli K, in particular its composition and biological activity. Methods. Lipopolysaccharide (LPS) was obtained from cells by water-phenol extraction, heterogeneity was determined by SDS-PAAG electrophoresis, monosaccharide and fatty acid compositions were determined by chromatography-mass spectrometry, and serological activity – by immunodiffusion in agar. Determination of the osmotic resistance of erythrocytes was carried out according to the research by Bazarnova et al. Results. In purified LPS, 29.46% carbohydrates, 4.9% nucleic acids, and 9.53% proteins were found. The content of 2-keto-3-deoxyoctonic acid (KDO) and heptose, characteristic of LPS components, was 0.03% and 5.64%, respectively. Identification of the monosaccharide composition indicates that galactose dominates in LPS – 70.87%. Fucose, ribose, and glucose were found in smaller quantities (11.86, 10.11, and 7.16%, respectively). The hydroxy acids 2-OH-C12:0 – 32.23%, 2-OH-C14:0 – 25.07% and 3-OH-C14:0 – 7.26% were identified in the composition of the LPS preparation under study. C14:0 – 10.69%, C17:0 – 5.35%, C16:0 – 3.15%, C15:0 – 3.04%, and unidentified fatty acid – 13.21% were also detected. SDS-PAGE electrophoresis showed that the studied E. coli LPS is represented by a heterogeneous population, which includes two main types of molecules: high-molecular-weight S-LPS with O-chains of various lengths and low- molecular-weight R-LPS, which does not contain O-specific polysaccharide chains. The tested preparation of E. coli LPS turned out to be pyrogen-free: it did not reach either the level of pyrogenicity or the level of “Pyrogenal” (pharmaceutical drug), the active component of which is Shigella typhi LPS. The determination of osmotic resistance of erythrocytes showed that a high percentage of hemolysis is observed in the erythrocytes of all donors after treatment with solutions of LPS preparations, both native and modified. Conclusions. The obtained data indicate a high biological potential of the influence of lipopolysaccharides on the resistance of erythrocytes, which gives reason to attribute this criterion to possible prognostic factors of the risk of osmotic lysis.